A solidifying agent for road construction and a preparation method and application thereof
Patent Information
- Application Number
- CN202410982179.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-22
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-07-22
AI Technical Summary
但是,无论是采用石灰来固结土壤还是采用水泥来固结土壤,生成C-S-H凝胶的过程都会引起被固结土壤的体积收缩,并且会随着C-S-H凝胶量增加,被固结的土壤的体积收缩率也相应增大
1、由于本申请采用水泥、硅酸钠和碳酸钙三种原料作为土壤固化剂,由于水泥能产生水化作用,形成氢氧化钙和C-S-H凝胶,并且硅酸钠和碳酸钙能与水泥反生反应,形成硅酸钙凝胶等,粘结固化土,填充到固化体的缝隙中,从而使土壤被固结,且不易产生体积收缩。
Smart Images

Figure BDA0004956399740000091 
Figure BDA0004956399740000101 
Figure BDA0004956399740000111
Abstract
Description
Technical Field
[0001] This application relates to the field of civil engineering materials technology, and more specifically, it relates to a curing agent for road construction, its preparation method, and its application. Background Technology
[0002] Soil is the primary building material for foundations, especially for highway foundations. It is well known that in road and building construction, the structure and quality of the foundation play a decisive role in the service life and load-bearing capacity of above-ground roads, bridges, and other structures. The specialized soil that constitutes the foundation is formed by consolidating soils of different properties. To ensure the foundation has sufficient strength and stability, and to enable the soil to meet construction requirements, soil processing is necessary. Therefore, various soil stabilizers and their application methods have been extensively studied.
[0003] Currently, lime and cement are commonly used materials for soil reinforcement, which can enhance soil strength, improve water stability, and increase engineering performance. However, regardless of whether lime or cement is used to consolidate the soil, the formation of CSH gel will cause volume shrinkage of the consolidated soil, and the volume shrinkage rate of the consolidated soil will increase accordingly with the increase of CSH gel content. When lime and / or cement-consolidated soil is used to prepare the subbase and base course of highways, this shrinkage will create many small cracks in its internal structure, thus impairing its water permeability and frost resistance. Furthermore, due to the reduced solidity of the subbase and base course, large cracks may appear in the asphalt or concrete pavement of the highway, seriously affecting the quality of the highway. The strength of lime-soil increases slowly and the strength increase is limited; cement-soil has lower strength, greater drying shrinkage, and poorer durability.
[0004] Regarding the aforementioned technologies, the inventors have discovered that using cement or lime alone as soil stabilization materials currently has limitations, such as low soil strength and high shrinkage rate after stabilization. Summary of the Invention
[0005] In order to achieve high strength and low shrinkage rate after soil solidification, this application provides a curing agent for road construction, its preparation method and application.
[0006] In a first aspect, this application provides a curing agent for road construction, employing the following technical solution: A curing agent for road construction comprises cement, sodium sulfate, and calcium carbonate in a mass ratio of 6-9:0.5-2:0.5-2.
[0007] By adopting the above technical solution, using cement, sodium sulfate, and calcium carbonate in a specific mass ratio as a curing agent, the cement can react with water in the slurry to generate various hydrates. These hydrates then undergo a series of physicochemical reactions with soil particles, improving the engineering properties of the soil. Specifically, minerals such as tricalcium silicate and dicalcium silicate in the cement react with water to generate hydrates such as calcium hydroxide and hydrated calcium silicate. These hydrates form fine crystals in the soil, filling the pores between soil particles, enhancing the cohesive force between particles, and making the soil denser. This improves the overall strength, impermeability, bearing capacity, and stability of the soil. Simultaneously, alkaline substances such as calcium hydroxide can react with clay minerals and other components in the soil, further... Sodium silicate improves soil structure and properties; it has good permeability and can quickly penetrate into the soil, reacting chemically with free calcium and magnesium ions in the soil. Furthermore, the sodium ions in sodium silicate can undergo ion exchange reactions with free calcium and magnesium ions in the soil, forming a stable calcium silicate gel that fixes soil particles in place, improving soil impermeability and durability. Sodium silicate also has a certain degree of hygroscopicity, helping the soil retain moisture and reducing soil shrinkage during drying. Calcium carbonate reacts with water to form calcium hydroxide, making the soil environment alkaline, which is conducive to the hydration reaction of cement and sodium silicate and the gelation process. Moreover, calcium carbonate powder can fill the tiny pores in the soil, thereby improving soil density and bearing capacity.
[0008] Optionally, the mass ratio of cement, sodium sulfate, and calcium carbonate in the curing agent is 8:1:1.
[0009] By adopting the above technical solution, cement, sodium silicate and calcium carbonate are mixed in a more precise mass ratio as a curing agent, which can achieve better soil curing effect, resulting in high soil strength, good impermeability and low drying shrinkage.
[0010] Optionally, rice husk ash is also added to the curing agent, and the mass ratio of rice husk ash to cement is 0.08-0.1:1.
[0011] By adopting the above technical solution, rice husk ash is produced by burning rice husks at a certain temperature. The lignin and cellulose of the rice husks are decomposed and burned away, leaving a porous silica skeleton. This increases the active surface of cement particles and promotes the cement hydration reaction. The cement hydration products adhere to the surface of the rice husk ash and form a network structure in the mixed system, thereby improving the mechanical properties of the soil. Moreover, rice husk ash contains highly active amorphous silica, giving it high activity similar to silica fume. Under certain conditions, rice husk ash has potential cementitious activity, which can promote the generation of cement hydration products, increase the hydration products in the solidified soil, and continuously fill the pores, making the solidified soil structure denser and increasing compressive strength. In addition, the reaction between rice husk ash and cement produces a porous, high specific surface area, honeycomb-like CSH gel. The porous structure can promote the infiltration of water and calcium ions from the outside into the pores. The large specific surface area and abundant pores can retain free water in the mud and slowly supply water during the cement hydration reaction stage, thereby delaying the chemical shrinkage caused by the cement hydration reaction.
[0012] Optionally, the rice husk ash undergoes the following pretreatment: A 20-25 wt% solution of trimethoxysilane in tert-butanol was mixed with rice husk ash and sonicated for 30-40 minutes to obtain a premixed solution. After surface treatment, aramid fibers are immersed in a 5-10% NMP solution of polyarylene ether nitrile for 20-30 minutes. Then, the temperature is raised to 120℃ and held for 20-25 minutes, raised to 180℃ and held for 50-60 minutes, raised to 200℃ and held for 50-60 minutes, raised to 280-300℃ and held for 1.5-2 hours. After cooling to room temperature, the fibers are cut to obtain modified aramid fibers. The premixed liquid is uniformly sprayed onto the modified aramid fiber and vacuum dried for 20-24 hours. The mass ratio of rice husk ash to modified aramid fiber is 1:1.5-2.
[0013] Rice husk ash has a porous structure and contains many hydrophilic groups. Therefore, when added to solidified soil, it does not significantly improve the soil's impermeability. By adopting the above-mentioned technical solution, a tert-butanol solution of trimethoxysilane is mixed with rice husk ash. Trimethoxysilane can diffuse into the rice husk ash and produce silanol groups after hydrolysis. The silica nanoparticles in rice husk ash also have many hydroxyl groups on their surface. Therefore, the silica nanoparticles and the silanol groups of trimethoxysilane can easily condense to form a hydrophobic layer on the rice husk ash, thereby reducing the impact of rice husk ash on the impermeability of the solidified soil.
[0014] Aramid fiber is a high-performance fiber with excellent properties such as high strength, high modulus, low density, chemical corrosion resistance, high temperature resistance, fatigue resistance, and dimensional stability. After surface treatment to remove the sizing agent, a layer of polyarylene ether nitrile crystals is coated onto the aramid surface using an impregnation and heating method. The polyarylene ether nitrile crystals growing on the surface improve the fiber's surface roughness and enhance the entanglement effect between the aramid fiber and rice husk ash, or even the soil, thereby improving the compatibility between the fiber and the soil. Furthermore, the incorporation of modified aramid fiber as the main reinforcing material allows for mutual support or overlap within the soil, serving as three-dimensional reinforcement. It provides soil with resistance to deformation, inhibits large deformation of soil, and improves soil strength. After loading rice husk ash and polyarylene ether nitrile crystals on its surface, the rice husk ash and polyarylene ether nitrile crystals on the surface can increase the interlocking between soil particles. Moreover, the polyarylene ether nitrile molecule contains functional groups such as aromatic cyclic ether bonds, which makes it have low surface energy, is not easily wetted by water, has good hydrophobicity, and has good mechanical strength. When subjected to tension, it can maintain high strength and stiffness and is not easy to deform. Polyarylene ether nitrile can improve the mechanical strength of aramid fibers and increase the interfacial effect between the premix and aramid fibers.
[0015] Optionally, the average length of the modified aramid fiber is 3-10 mm.
[0016] By adopting the above technical solution, the modified aramid fiber, at the above length, is easy to attach to rice husk ash and can form interlocking reinforcing ribs in the solidified soil, thereby improving the crack resistance and drying shrinkage of the solidified soil.
[0017] Optionally, the surface treatment method for the aramid fiber is as follows: immersing the aramid fiber in a solution prepared by mixing acetone, ethanol and deionized water in a volume ratio of 4:3.5:2.5 for 24-26 hours, then washing with ethanol solution and deionized water in sequence, and drying.
[0018] By adopting the above technical solution, aramid fibers are chemically inert due to the obstruction of benzene rings in their molecular chains. Therefore, acetone and other substances are first used to remove impurities such as sizing agents and desizing agents from their surface, which facilitates the bonding of aramid fibers with polyarylene ether nitrile.
[0019] Optionally, the curing agent may also contain glass powder with a particle size of 10-40 μm, and the mass ratio of glass powder to cement is 0.1-0.2:1.
[0020] By adopting the above technical solution, sodium sulfate in the curing agent can act as an alkali activator. The sulfate ions in sodium sulfate and the calcium ions in the soil can promote the reaction between the active ingredients in the glass powder and the cement hydration products to form needle-shaped ettringite, which fills the gaps in the solidified soil, increases the density of the solidified body, and thus improves the strength. The glass contains active silica, which reacts with cement to form calcium hydroxide and CSH gel. Because the CSH gel has a small size range, it can effectively fill the capillaries in the cement stone and the tiny gaps between the aggregates, making the composition of the cement stone more compact and dense, thereby reducing water penetration, increasing compressive strength, and reducing drying shrinkage.
[0021] Secondly, this application provides a method for preparing a curing agent for road construction, employing the following technical solution: A method for preparing a curing agent for road construction includes the following steps: mixing cement, sodium sulfate, calcium carbonate, rice husk ash and glass powder, stirring for 4-5 minutes to obtain the curing agent.
[0022] By adopting the above technical solution, the preparation method is simple and easy to operate.
[0023] Thirdly, this application provides an application of a curing agent used in road construction in dry-mixed solidified soil, employing the following technical solution: The application of a curing agent for road construction in dry-mixed hardened soil, wherein the curing agent is added to the dry-mixed hardened soil at a rate of 20-21%.
[0024] By adopting the above technical solution, adding the curing agent to the dry-mixed solidified soil in a specific amount can make the dry-mixed solidified soil form a hard soil body. The solidified soil does not shrink in volume, which improves the soil's waterproof permeability and frost resistance, thereby strengthening the solidity of the subbase and base course, avoiding cracks in the road surface, and improving the construction quality of the highway.
[0025] Fourthly, this application provides an application of a curing agent for road construction in fluidized solidified soil, employing the following technical solution: The application of a curing agent for road construction in fluidized solidified soil, wherein the curing agent is added at a rate of 15-16% in the fluidized solidified soil.
[0026] By adopting the above technical solution, adding the curing agent to the fluidized solidified soil in a specific amount can make the fluidized solidified soil form a hard soil body. The solidified soil does not produce volume shrinkage, which improves the soil's waterproof permeability and frost resistance, thereby strengthening the solidity of the subbase and base course, avoiding cracks in the road surface, and improving the construction quality of the highway.
[0027] In summary, this application has the following beneficial effects: 1. Since this application uses cement, sodium silicate and calcium carbonate as three raw materials as soil stabilizers, cement can produce hydration to form calcium hydroxide and CSH gel, and sodium silicate and calcium carbonate can react with cement to form calcium silicate gel, etc., which bind and stabilize the soil and fill the gaps in the stabilized body, thereby consolidating the soil and making it less prone to volume shrinkage.
[0028] 2. In this application, it is preferred to add rice husk ash to the curing agent, which can buffer moisture and continuously release it, reducing the volume shrinkage of the cured soil caused by drying. In addition, the rice husk ash is pretreated to make it hydrophobic, which improves its influence on the impermeability of the cured soil. Furthermore, the rice husk ash adheres to the aramid fiber, which improves the crack resistance of the cured soil and reduces drying shrinkage.
[0029] 3. In this application, glass powder is preferably added to the curing agent, which not only acts as a filler, but also reacts with cement hydration products under the activation of sodium sulfate to generate needle-like ettringite, which fills the gaps, increases density, improves strength, and reduces impermeability. Detailed Implementation
[0030] The following embodiments provide a further detailed description of this application. Example
[0031] Example 1: A curing agent for road construction, comprising 800g cement, 100g sodium sulfate and 100g calcium carbonate, wherein the cement is Conch brand P.O42.5 silicate cement and the calcium carbonate has a particle size of 400 mesh; the preparation method of the curing agent for road construction includes the following steps: mixing cement, sodium sulfate and calcium carbonate, stirring for 5 minutes to prepare the curing agent.
[0032] Example 2: A curing agent for road construction, comprising 600g cement, 200g sodium sulfate and 200g calcium carbonate, wherein the cement is Conch brand P.O42.5 silicate cement and the calcium carbonate has a particle size of 400 mesh; the preparation method of the curing agent for road construction includes the following steps: mixing cement, sodium sulfate and calcium carbonate, stirring for 4 minutes to prepare the curing agent.
[0033] Example 3: A curing agent for road construction, comprising 900g cement, 50g sodium sulfate and 50g calcium carbonate, wherein the cement is Conch brand P.O42.5 silicate cement and the calcium carbonate has a particle size of 400 mesh; the preparation method of the curing agent for road construction includes the following steps: mixing cement, sodium sulfate and calcium carbonate, stirring for 4 minutes to prepare the curing agent.
[0034] Example 4: A curing agent for road construction, comprising 800g cement, 100g sodium sulfate, 100g calcium carbonate and 80g rice husk ash. The cement is Conch brand P.O42.5 silicate cement, and the calcium carbonate has a particle size of 400 mesh. The rice husk ash is prepared as follows: the rice husks are washed three times with distilled water, dried at 110℃ for 24h, then immersed in a 5wt% citric acid solution, stirred at 50℃ for 2h, then removed, rinsed and dried, and then calcined at 800℃ for 30min. Its chemical composition is shown in Table 1.
[0035] The preparation method of the above-mentioned curing agent for road construction includes the following steps: mixing cement, sodium sulfate, calcium carbonate and rice husk ash, stirring for 5 minutes to prepare the curing agent.
[0036] Example 5: A curing agent for road construction, comprising 800g cement, 100g sodium sulfate, 100g calcium carbonate and 64g rice husk ash. The cement is Conch brand P.O42.5 silicate cement, and the calcium carbonate has a particle size of 400 mesh. The rice husk ash is prepared as follows: the rice husks are washed three times with distilled water, dried at 110℃ for 24h, then immersed in a 5wt% citric acid solution, stirred at 50℃ for 2h, then removed, rinsed and dried, and then calcined at 800℃ for 30min. Its chemical composition is shown in Table 1.
[0037] The preparation method of the above-mentioned curing agent for road construction includes the following steps: mixing cement, sodium sulfate, calcium carbonate and rice husk ash, stirring for 5 minutes to prepare the curing agent.
[0038] Example 6: A curing agent for road construction, comprising 800g cement, 100g sodium sulfate, 100g calcium carbonate, 80g rice husk ash, and 160g glass powder with a particle size of 40μm. The cement is Conch brand P.O42.5 silicate cement, and the calcium carbonate has a particle size of 400 mesh. The rice husk ash is prepared as follows: rice husks are washed three times with distilled water, dried at 110℃ for 24h, then immersed in a 5wt% citric acid solution, stirred at 50℃ for 2h, then removed, rinsed and dried, and then calcined at 800℃ for 30min. The glass powder is obtained by washing, drying, crushing, and ball milling waste beer bottles. Its chemical composition is shown in Table 1.
[0039] Table 1 Chemical composition of rice husk ash and glass powder Rice husk ash 87.2 0.15 0.16 0.55 0.35 1.12 3.68 glass powder 69.16 2.94 1.46 10.52 1.16 12.13 1.25 The preparation method of the above-mentioned curing agent for road construction includes the following steps: mixing cement, sodium sulfate, calcium carbonate, rice husk ash and glass powder, stirring for 5 minutes to prepare the curing agent.
[0040] Example 7: A curing agent for road construction, comprising 800g cement, 100g sodium sulfate, 100g calcium carbonate, 80g rice husk ash, and 80g glass powder with a particle size of 10μm. The cement is Conch brand P.O42.5 silicate cement, and the calcium carbonate has a particle size of 400 mesh. The rice husk ash is prepared as follows: rice husks are washed three times with distilled water, dried at 110℃ for 24h, then immersed in a 5wt% citric acid solution, stirred at 50℃ for 2h, then removed, rinsed and dried, and then calcined at 800℃ for 30min. The glass powder is obtained by washing, drying, crushing, and ball milling waste beer bottles. Its chemical composition is shown in Table 1.
[0041] The preparation method of the above-mentioned curing agent for road construction includes the following steps: mixing cement, sodium sulfate, calcium carbonate, rice husk ash and glass powder, stirring for 5 minutes to prepare the curing agent.
[0042] Example 8: A curing agent for road construction, differing from Example 6 in that the rice husk ash undergoes the following pretreatment: A premixed solution was prepared by mixing 180g of a 25wt% trimethoxysilane tert-butanol solution with 80g of rice husk ash and sonicating for 40min. Aramid fibers were immersed in a solution prepared by mixing acetone, ethanol and deionized water in a volume ratio of 4:3.5:2.5 for 24 hours. Then, the fibers were washed with ethanol solution (ethanol and deionized water mixed in a volume ratio of 4:1) and deionized water in sequence and dried. The aramid fibers were selected from Hubei Tengdi New Materials, model TD-023, with a length of 51 mm. Surface-treated aramid fibers were immersed in a 10 wt% NMP solution of polyarylene ether nitrile for 20 min, then heated to 120 °C and held for 20 min, then heated to 180 °C and held for 50 min, then heated to 200 °C and held for 50 min, then heated to 280 °C and held for 1.5 h, cooled to room temperature, and cut to obtain modified aramid fibers with an average length of 10 mm. The polyarylene ether nitrile was selected from Guangdong Wengjiang Chemical Reagent Co., Ltd., model PA92396. The premixed liquid was evenly sprayed onto 120g of modified aramid fiber and vacuum dried for 20-24h. The mass ratio of rice husk ash to modified aramid fiber was 1:1.5.
[0043] Example 9: A curing agent for road construction, differing from Example 6 in that the rice husk ash undergoes the following pretreatment: A premixed solution was prepared by mixing 200g of a 25wt% trimethoxysilane tert-butanol solution with 80g of rice husk ash and sonicating for 30min. Aramid fibers were immersed in a solution prepared by mixing acetone, ethanol and deionized water in a volume ratio of 4:3.5:2.5 for 26 hours. Then, the fibers were washed sequentially with ethanol solution (ethanol and deionized water mixed in a volume ratio of 4:1) and deionized water, and dried. The aramid fibers were selected from Hubei Tengdi New Materials, model TD-023, with a length of 51 mm. Surface-treated aramid fibers were immersed in a 5 wt% NMP solution of polyarylene ether nitrile for 30 min, then heated to 120 °C and held for 25 min, then heated to 180 °C and held for 60 min, then heated to 200 °C and held for 60 min, then heated to 300 °C and held for 2 h, cooled to room temperature, and cut to obtain modified aramid fibers with an average length of 3 mm. The polyarylene ether nitrile was selected from Guangdong Wengjiang Chemical Reagent Co., Ltd., model PA92396. The premixed liquid was evenly sprayed onto 160g of modified aramid fiber and vacuum dried at 80℃ for 24h. The mass ratio of rice husk ash to modified aramid fiber was 1:2.
[0044] Example 10: A curing agent for road construction, which differs from Example 8 in that an equal amount of deionized water is used instead of a tert-butanol solution containing trimethoxysilane.
[0045] Example 11: A curing agent for road construction, which differs from Example 8 in that the aramid fibers are not surface-treated.
[0046] Example 12: A curing agent for road construction, which differs from Example 8 in that the aramid fibers are not treated with polyaryletheronitrile, and the premixed liquid is sprayed onto the surface of the surface-treated aramid fibers.
[0047] Comparative Example Comparative Example 1: A curing agent for road construction, which differs from Example 1 in that an equal amount of sodium sulfate is used instead of calcium carbonate.
[0048] Comparative Example 2: A curing agent for road construction, which differs from Example 1 in that an equal amount of calcium carbonate is used instead of sodium sulfate.
[0049] Comparative Example 3: A road soil stabilizer, wherein undisturbed water-quenched slag (purchased from Shaanxi Longmen Iron and Steel Plant) was ground into a specific surface area of 439 m² using a ball mill. 2 The ultrafine powder has a density of 2.83 g / cm³. 3The average particle size was 14.120 μm. The slaked lime (purchased from Jingyang Lime Plant in Shaanxi Province) was sieved through a 2.36 mm sieve. 68.57 kg of ultrafine slag powder and 28.57 kg of sieved slaked lime powder were mixed, and 2.86 kg of Class III industrial sodium sulfate (purchased from Shaanxi Baohua Chemical Co., Ltd.) was added and stirred evenly to obtain the soil stabilizer of this invention. In this embodiment, the weight ratio of slag, slaked lime, and sodium sulfate was 12:5:0.5.
[0050] Application examples of dry-mixed solidified soil Application Example 1: A dry-mixed solidified soil, comprising 1000g of the solidifying agent prepared in Example 1, 3500g of yellow mud, and 500g of water. The preparation method is as follows: mix the solidifying agent and yellow mud evenly, add water, and stir evenly.
[0051] Application Example 2-17: A dry-mixed solidified soil, the specific raw material dosage and solidifying agent selection are shown in Table 2. In Application Example 16, the cement is P.O52.5 silicate cement, and in Application Example 17, the slaked lime particle size is 2.3mm.
[0052] Table 2 shows the raw material consumption of dry-mixed solidified soil in Application Examples 1-17. Application Example 1 1000 (Example 1) 3500 500 Application Example 2 1000 (Example 2) 3500 500 Application Example 3 1000 (Example 3) 3500 500 Application Example 4 1080 (Example 4) 3780 540 Application Example 5 1064 (Example 5) 3724 532 Application Example 6 1240 (Example 6) 4340 620 Application Example 7 1160 (Example 7) 4060 580 Application Example 8 1240 (Example 8) 4340 620 Application Example 9 1240 (Example 9) 4340 620 Application Example 10 1240 (Example 10) 4340 620 Application Example 11 1240 (Example 11) 4340 620 Application Example 12 1240 (Example 12) 4340 620 Application Example 13 1000 (Comparative Example 1) 3500 500 Application Example 14 1000 (Comparative Example 2) 3500 500 Application Example 15 1000 (Comparative Example 3) 3500 500 Application Example 16 1000 (cement) 3500 500 Application Example 17 1000 (hydrated lime) 3500 500 The dry-mixed solidified soil prepared in Application Examples 1-17 was tested according to the following standards, and the test results are recorded in Table 3.
[0053] 1. Compressive strength and flexural strength: tested in accordance with GB / T50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete"; 2. Consolidation shrinkage rate: Tested according to DB42 / T1218-2016 "Synchronous Grouting Materials for Shield Tunneling"; 3. Water absorption rate: Tested in accordance with GB / T50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete".
[0054] Table 3 Performance Tests of Dry-Mixed Solidified Soil Containing Hardener Table 3 shows that the compressive strength of the dry-mixed solidified soils used in Examples 1-3 reached over 9.8 MPa, with a consolidation shrinkage rate of less than 5% and a water absorption rate of no more than 1%, and the solidified soil was not prone to cracking.
[0055] In Application Examples 4 and 5, rice husk ash was added to the curing agent used in the dry-mixed solidified soil. Compared with Application Example 1, the dry-mixed solidified soil obtained in this way had increased density and enhanced resistance to drying shrinkage.
[0056] In Application Examples 6 and 7, not only rice husk ash was added, but glass powder was also used. The data in Table 3 shows that the compressive strength of the solidified soil prepared in Application Examples 6 and 7 is higher than that in Application Examples 1 and 4, the density is further enhanced, the drying shrinkage rate is reduced, and the impermeability is improved.
[0057] In Application Examples 8 and 9, rice husk ash was further treated with trimethoxysilane, aramid fiber, etc. Compared with Application Example 6, the compressive strength of the solidified soil in Application Examples 8 and 9 was further enhanced and the solidification shrinkage rate decreased.
[0058] In Application Example 10, when rice husk ash was pretreated in the curing agent, a tert-butanol solution of trimethoxysilane was not used. As a result, the water absorption rate of the cured soil increased and the impermeability decreased.
[0059] In Application Example 11, the curing agent used did not pretreat the aramid fibers during the rice husk ash pretreatment. However, in Application Example 12, the curing agent sprayed the premixed liquid onto the surface-treated aramid fibers without using polyaryletheronitrile. The data in Table 3 show that the flexural strength of the dry-mixed cured soil in Application Example 11 decreased, possibly because the surface of the aramid fibers was untreated and relatively smooth, resulting in a weakened interfacial force with the cured soil. In Application Example 12, the water absorption rate of the cured soil increased, leading to a decrease in flexural strength.
[0060] In Application Examples 13 and 14, the curing agents prepared using Comparative Examples 1 and 2 respectively are shown in Table 3. It can be seen that using sodium sulfate instead of calcium carbonate, or using calcium carbonate instead of sodium sulfate, cannot achieve the effect of the compounding of cement, sodium sulfate and calcium carbonate.
[0061] In Application Example 15, slag powder, quicklime, and sodium sulfate were used as curing agents, but their curing effect was not as good as that of this application. In Application Examples 16 and 17, quicklime and cement were used alone as curing agents, and the compressive strength of the cured soil was not good.
[0062] Application examples of fluidized solidified soil Application Example 18: A fluidized solidified soil, comprising 1000g of the solidifying agent prepared in Example 1, 2000g of fine sand (fineness modulus of 2.2-2.6), 1000g of yellow mud, 1666g of pea gravel (particle size of 2cm), and 833g of water.
[0063] Application Examples 19-34: A fluidized solidified soil, which differs from Application Example 18 in that the amount of raw materials and the selection of curing agent are shown in Table 4.
[0064] Table 4. Raw material consumption for application examples 18-34: fluidized solidified soil The dry-mixed solidified soil prepared in Application Examples 18-34 was tested according to the following standards, and the test results are recorded in Table 5.
[0065] 1. Compressive strength and flexural strength: tested in accordance with GB / T50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete"; 2. Consolidation shrinkage rate: Tested according to DB42 / T1218-2016 "Synchronous Grouting Materials for Shield Tunneling"; 3. Water absorption rate: Tested in accordance with GB / T50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete".
[0066] Table 5 Performance Tests of Fluidized Solidified Soil Containing Solidifying Agent In Application Examples 18-20, the solidifying agents prepared in Examples 1-3 were used in the dry-mixed solidified soil. These agents had high compressive strength, a consolidation shrinkage rate of less than 1.5%, and a water absorption rate of no more than 1%. The solidified soil was not prone to cracking.
[0067] Rice husk ash was added in Examples 4-5, and glass powder was used in Examples 6-7 in addition to rice husk ash. The compressive strength and other properties of Application Examples 23-24 were better than those of Application Examples 21-22, while the compressive strength and other properties of the solidified soil in Application Examples 21-22 were better than those of Application Example 18. This shows that the addition of rice husk ash and glass powder can further improve the compactness of the solidified soil and reduce solidification shrinkage.
[0068] Compared with Application Example 23, Application Examples 25 and 26 further treated the rice husk ash with aramid fibers, etc. The data in Table 5 show that the compressive strength and flexural strength of the fluidized solidified soil were further improved, the impermeability was enhanced, and the shrinkage rate was reduced.
[0069] Compared with Application Example 26, Application Examples 27-29 show that the performance of fluidized solidified soil is slightly reduced when different methods are used to pretreat rice husk ash.
[0070] Application Examples 30 and 31 used curing agents prepared by Comparative Examples 1 and 2, respectively. The data in Table 3 shows that neither using sodium sulfate to replace calcium carbonate nor using calcium carbonate to replace sodium sulfate can achieve the effect of a compound of cement, sodium sulfate and calcium carbonate.
[0071] Application Example 32 uses the curing agent prepared in Comparative Example 3, which consists of slag, sodium sulfate, and quicklime. Application Example 33 uses cement, and Application Example 34 uses quicklime. By comparison, it can be seen that the curing agents prepared in Application Examples 18-20 using cement, sodium sulfate, and calcium carbonate have a better soil curing effect.
[0072] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. A curing agent for road construction, characterized in that, The curing agent comprises cement, sodium sulfate, and calcium carbonate in a mass ratio of 6-9:0.5-2:0.5-2, and rice husk ash is also added to the curing agent, with the mass ratio of rice husk ash to cement being 0.08-0.1:
1. The rice husk ash undergoes the following pretreatment: A 20-25 wt% solution of trimethoxysilane in tert-butanol was mixed with rice husk ash and sonicated for 30-40 minutes to obtain a premixed solution. After surface treatment, aramid fibers are immersed in a 5-10% NMP solution of polyarylene ether nitrile for 20-30 minutes. Then, the temperature is raised to 120℃ and held for 20-25 minutes, raised to 180℃ and held for 50-60 minutes, raised to 200℃ and held for 50-60 minutes, raised to 280-300℃ and held for 1.5-2 hours, cooled to room temperature, and cut to obtain modified aramid fibers. The premixed liquid is uniformly sprayed onto the modified aramid fiber and vacuum dried for 20-24 hours. The mass ratio of rice husk ash to modified aramid fiber is 1:1.5-2.
2. The curing agent for road construction according to claim 1, characterized in that: The mass ratio of cement, sodium sulfate, and calcium carbonate in the curing agent is 8:1:
1.
3. The curing agent for road construction according to claim 1, characterized in that: The modified aramid fiber has an average length of 3-10 mm.
4. The curing agent for road construction according to claim 1, characterized in that: The surface treatment method for the aramid fiber is as follows: the aramid fiber is immersed in a solution prepared by mixing acetone, ethanol and deionized water in a volume ratio of 4:3.5:2.5 for 24-26 hours, and then washed with ethanol solution and deionized water in sequence, and dried.
5. The curing agent for road construction according to claim 1, characterized in that: The curing agent also contains glass powder with a particle size of 10-40μm, and the mass ratio of glass powder to cement is 0.1-0.2:
1.
6. The method for preparing the curing agent for road construction according to any one of claims 1-5, characterized in that: Includes the following steps: The curing agent is prepared by mixing cement, sodium sulfate, calcium carbonate, rice husk ash and glass powder and stirring for 4-5 minutes.
7. The application of the curing agent for road construction according to any one of claims 1-5 in dry-mixed solidified soil, characterized in that: The amount of the curing agent added to the dry-mixed solidified soil is 20-21%.
8. The application of the curing agent for road construction according to any one of claims 1-5 in fluidized solidified soil, characterized in that: The amount of the curing agent added to the fluidized solidified soil is 15-16%.
Citation Information
Patent Citations
Method for manufacturing soil brick having high strength and low absorption rate using unfiring forming method
WO2015156541A1